Diagnostic and prognostic implications of myocardial work in cardiac amyloidosis and in genetic and non-genetic cardiomyopathies with hypertrophic phenotype. (4th February 2022) - Palmiero, G; Rubino, M; Monda, E; Lioncino, M; Verrillo, F; Vetrano, E; Caiazza, M; Fusco, A; Cirillo, A; Dongiglio, F; Ascione, L; Caso, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND & PURPOSE. Cardiac amyloidosis (CA) is an infiltrative disorder characterized by left ventricular (LV) thickening with early systolic and diastolic dysfunction. Due to it poor prognosis, and the beneficial impact of novel treatments when started in early stages of disease, its forward detection is crucial. Aim of this study is comparing the diagnostic accuracy of classical and novel echocardiographic parameters in detecting CA among other forms of genetic and non-genetic cardiomyopathies with hypertrophic phenotype. METHODS. We enrolled 50 pts with CA (26 AL and 24 wtATTR) and 75 phenocopies (LVH group) [25 hypertrophic cardiomyopathy (HCM) pts, 25 hypertensive (HypCM) pts, and 25 pts with non-severe aortic stenosis (AS)]. Standard and novel LV morpho-functional echo parameters [LV ejection fraction (LVEF), myocardial contraction fraction (MCF), global longitudinal strain (GLS), relative regional strain ratio (RRSR), ejection fraction on strain ratio (EFSR)], and novel Myocardial Work (MW) parameters [Global Work Index (GWI), Global Constructive Work (GCW), Global Wasted Work (GWW), Global Work Efficiency (GWE)] were analyzed. RESULTS. LV standard, novel and MW-derived systolic parameters were more impaired in CA compared to LVH group. At ROC curve analysis, GCW showed the best performance in discriminating CA from other forms of LVH (AUC 0.886; 95% CI: 0.819-0.954; P < 0.0001), with a cut-off value < 1473 mmHg% showing 90% of sensitivity and 82% of specificity). At linear regression analysis, GCW correlated with many echocardiographic parameters (IVSD, PWD, RWT ratio, LVMi, MCF, LVESV, LVEF, EFSR and RRSR). At multivariate analysis, PWD (P < 0, 029) and RWT ratio (p < 0, 014) were the only parameters associated with GCW. At 24 months follow-up, there were 15 deaths in CA and 4 in LVH group. At Kaplan-Meier analysis the overall survival free of cardiovascular death was reduced in the lowest GCW interquartile ranges (log-rank χ2 21.5; p < 0.0001). At Cox hazard ratio analysis, GCW was the only prognostic parameter associated with cardiovascular mortality (β 1.006; 95% CI: 1.003-1.009; P < 0.0001). CONCLUSIONS. Despite CA and LVH patients shows a similar phenotype, the systolic function differs greatly. In the present study, the GCW showed the best ability in detecting CA among other forms of LVH. Its reduction in CA seems reflect the infiltrative burden and its consequences on myocardial deformation properties, while its reduction in LVH group has been attributed elsewhere to fibrotic derangement. GCW showed to be a promising novel diagnostic and prognostic factor in this setting.